What do we know about the psychosocial issues associated with cancer during pregnancy? A scoping review and gap analysis - Faith Gibson; Karen Poole; Ann Robinson; Emma Ream; Jo Armes; Afrodita Marcu; Jenny Harris; Catherine Treena Parsons; Sherin Varghese (BMJ Open, 2023)
Objectives There is a global increase in the number of women diagnosed with cancer during their pregnancy and a nascent evidence base to guide their supportive care. The purposes of this study were to (1) map research on the psychosocial issues affecting women and their partners on diagnosis and treatment for cancer during pregnancy; (2) determine available supportive care or educational interventions; and (3) identify knowledge gaps for future research and development.Design Scoping review.Search strategy Six databases were searched (Scopus, CINAHL, PsycINFO, Medline, Intermid, Maternal and Infant Health) to retrieve primary research (January 1995 to November 2021) investigating women and/or their partner’s decision-making and their psychosocial outcomes during and after pregnancy.Data extraction and synthesis Sociodemographic, gestational and disease characteristics of participants and psychosocial issues identified were extracted. Leventhal’s self-regulatory model of illness provided a framework for mapping study findings enabling evidence synthesis and gap analysis.Results Twelve studies were included, conducted in eight countries in six continents. Most women (70% of 217) were diagnosed with breast cancer during pregnancy. Reporting of sociodemographic, psychiatric, obstetric and oncological characteristics that are important in assessing psychosocial outcomes was inconsistent. None of the studies had a longitudinal design and no supportive care or educational interventions were identified. The gap analysis highlighted the lack of evidence about pathways to diagnosis, impact of late effects and how internal/social resources may affect outcomes.Conclusions Research has focused on women with gestational breast cancer. Little is known about those diagnosed with other cancers. We encourage future study designs to capture data on sociodemographic, obstetric, oncological and psychiatric characteristics and adopt a longitudinal approach to explore the longer term psychosocial impact on women and their families. Future research should include outcomes that are meaningful for women (and their partners) and draw on international collaboration to accelerate progress in this field.